FACTORS AFFECTING THE SYSTEM OF ORGANIZATION OF WORK OF THE SCHOOL PEDAGOGICAL TEAM (Conferencea, 2023)
Currently, the organization of labor in schools is important in ensuring the quality of education, and this article analyzes the factors affecting the organization of labor of the pedagogical community.